Adaptation of the Chemical Percolation Devolatilization Model for Low Temperature Pyrolysis in a Fluidized Bed Reactor. Issue 2 (25th January 2022) - Pielsticker, S.; Ontyd, C.; Kreitzberg, T.; Hatzfeld, O.; Schiemann, M.; Scherer, V.; Kneer, R.
ABSTRACT: In the present study, the CPD model originally developed based on predictions from heated grid (HGR) and entrained flow (EFR) experiments, has been adapted to analyze pyrolysis kinetics in a small-scale fluidized bed reactor. Impacts of particle feed, particle heat up as well as tar cracking reactions in the gas phase are considered. Furthermore, an optimized solver structure allows a time step independent solution and enables the use of implicit methods. A comparison with experimental results is undertaken for pulverized Rhenish lignite fuel particles in the temperature range from 673 to 973 K in N2 atmosphere. The comparison between simulated and experimentally derived volatile release rates reveals a good agreement, indicating that the high temperature derived kinetic parameters from HRG and EFR experiments can be extrapolated to lower temperatures. Nevertheless, discrepancies in the tar to light gas ratio occur with the proposed model implementation.